2016
DOI: 10.3892/mco.2016.738
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy continuity and incidence of febrile neutropenia with CHOP therapy in an outpatient setting

Abstract: Abstract. The cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP) regimen is considered to be a standard treatment for non-Hodgkin's lymphoma (NHL). Patients receiving CHOP chemotherapy often experience febrile neutropenia (FN) due to myelotoxicity. The proper management of FN is essential to guarantee a positive outcome of the NHL treatment. Therefore, the present study retrospectively examined chemotherapy continuity and the incidence of FN during CHOP therapy in an outpatient setting. The sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Hematologic toxicities from chemotherapy may generally occur from the first to eighteenth week and most commonly arise in the fifth week or at the end of the second cycle. 29,30 The present study found that hematologic toxicities progressed at the end of the second cycle of chemotherapy, where the grade 3 toxicity increased dramatically from 0 to 37.50%. This might occur because the chemotherapy drugs, in addition to destroying the cancer cells, also kill progenitor cells that produce granulocytes, erythrocytes, and platelets in peripheral blood circulation.…”
Section: Discussionmentioning
confidence: 51%
“…Hematologic toxicities from chemotherapy may generally occur from the first to eighteenth week and most commonly arise in the fifth week or at the end of the second cycle. 29,30 The present study found that hematologic toxicities progressed at the end of the second cycle of chemotherapy, where the grade 3 toxicity increased dramatically from 0 to 37.50%. This might occur because the chemotherapy drugs, in addition to destroying the cancer cells, also kill progenitor cells that produce granulocytes, erythrocytes, and platelets in peripheral blood circulation.…”
Section: Discussionmentioning
confidence: 51%
“…Toxicity events often appear in the fifth week or at the end of the second cycle. 16 Cycles of chemotherapy are reported to be directly proportional to the severity of toxicity. A more significant number of chemotherapy cycles, the patient experience more severe toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects caused by the administration of antineoplastic drugs usually develop after the first cycle of chemotherapy, as a consequence of the high doses administered. There is a cumulative effect that remains throughout the treatment, which can lead to weight loss and increased vulnerability to potential infections 4,5,6 .…”
Section: Efecto Con La Suplementación De Vitamina C Sobre La Neutropementioning
confidence: 99%